ANALISIS USAHATANI DAN EFISIENSI PEMASARAN KOPI (Coffea sp) DI KECAMATAN PULAU PANGGUNG KABUPATEN TANGGAMUS - Ova Lestari; Ali Ibrahim Hasyim; Eka Kasymir (Lampung University, 2017)
This research aims to know the coffee farming, the formation process of coffee prices at farmer level, the coffee marketing channels, and marketing efficiency of coffee in Pulau Panggung subdistrict of Tanggamus Regency. This research was conducted in Gunung Megang village and Sri Mengantin village by involving 66 coffee farmers and following the flow of marketing, namely traders and trade collectors. Data analysis methods used in this research are a qualitative descriptive analysis and quantitative descriptive analysis including business farming (R/C ratio) and the S-C-P (Structure, Conduct, dan Perfomance) to analyze the organization of the market. The results showed that R/C ratio of >1, meaning that the farming of coffee was worthy to be cultivated and gave benefit. Farmers did not apply hedging system for their products. The coffee marketing channels in Pulau Panggung sub district of Tanggamus regency was as the following: farmers – large trader merchants– collectors – exporters. The marketing of coffee in Pulau Panggung sub district of Tanggamus Regency was not efficient, although the producer share reached more than 80%, the ratio of profit margin (RPM) on every marketing institution did not spread evenly. Key words: coffee, efficiency, farming, marketing